Novel 3D-Printed Dressings of Chitosan-Vanillin-Modified Chitosan Blends Loaded with Fluticasone Propionate for Treatment of Atopic Dermatitis - Georgia Michailidou; Dimitrios N. Bikiaris (MDPI AG, 2022)
In the present study, the blends of CS and Vanillin-CS derivative (VACS) were utilized for the preparation of printable inks for their application in three-dimensional (3D) printing procedures. Despite the synergic interaction between the blends, the addition of ι-carrageenan (iCR) as a thickening agent was mandatory. Their viscosity analysis was conducted for the evaluation of the optimum CS/VACS ratio. The shear thinning behavior along with the effect of the temperature on viscosity values were evident. Further characterization of the 3D-printed structures was conducted. The effect of the CS/VACS ratio was established through swelling and contact angle measurements. An increasing amount of VACS resulted in lower swelling ability along with higher hydrophobicity. Fluticasone propionate (FLU), a crystalline synthetic corticosteroid, was loaded into the CS/VACS samples. The drug was loaded in its amorphous state, and consequently, its in vitro release was significantly enhanced. An initial burst release, followed by a sustained release profile, was observed.